2021
DOI: 10.1128/jmbe.v22i1.2385
|View full text |Cite
|
Sign up to set email alerts
|

Student Engagement Declines in STEM Undergraduates during COVID-19–Driven Remote Learning

Abstract: We examined how the shift in learning environment from in-person to online classes, due to the COVID-19 pandemic, impacted three constructs of student engagement: behavioral engagement, including students’ frequency of participating in class discussions, meeting with instructors, and studying with peers outside of class; cognitive engagement, including students’ sense of belonging and self-efficacy; and emotional engagement, including students’ attitudes toward science, their perceived value of the course, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
90
2
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(102 citation statements)
references
References 48 publications
7
90
2
3
Order By: Relevance
“…This result is corroborated by the exclusive and massive adoption of e-learning during the confinement and post-confinement periods of several waves of outbreaks of COVID-19 variants. This finding of our review contradicts those of other studies conducted during the COVID-19 pandemic [41,42].…”
Section: Summary Of Evidencecontrasting
confidence: 99%
See 1 more Smart Citation
“…This result is corroborated by the exclusive and massive adoption of e-learning during the confinement and post-confinement periods of several waves of outbreaks of COVID-19 variants. This finding of our review contradicts those of other studies conducted during the COVID-19 pandemic [41,42].…”
Section: Summary Of Evidencecontrasting
confidence: 99%
“…Wester et al [41] in 2021 reported a significant decrease in the overall engagement score calculated from students' behavioral, cognitive, and emotional engagement scores during the pandemic. Moreover, Chan et al [42] in 2021 found that 55% of nursing students were not highly engaged in an online course during the COVID-19 pandemic.…”
Section: Summary Of Evidencementioning
confidence: 99%
“…Several publications have reported that students were less engaged (Perets et al, 2020;Wester et al, 2021) and struggled with their motivation to study after the transition to remote learning in Spring 2020 (Al-Tammemi et al, 2020;Gillis and Krull, 2020;Means and Neisler, 2020;Petillion and McNeil, 2020), although one study on public health students at Georgia State University did not report lower motivation among students (Armstrong-Mensah et al, 2020), perhaps because of the heightened awareness of the relevance of public health during a global pandemic. It has also been demonstrated that the transition to remote learning had a negative impact on student relationship-building, specifically the extent to which students interact with each other in and out of class (Jeffery and Bauer, 2020;Means and Neisler, 2020), and on students' sense of belonging in the class (Means and Neisler, 2020;Wester et al, 2021). In response to the pandemic, several universities changed course policies to extend the deadline for course withdrawals or to allow greater access to pass/fail grading options (Burke, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Experienced instructors' focus on kindness may be due to lower stress levels, allowing them more cognitive freedom to focus on the positive aspects in their memories (Weinstein and Ryan, 2011). One reason that experienced instructors may have had more difficulty with student behavior is because they knew what to expect from standard online participation, and this was not mirrored in ERT (Wester et al, 2021). Unsurprisingly, faculty without experience teaching online were more likely to report that learning or refining a technology skill was an unexpected benefit, because experienced online instructors are likely to be familiar and comfortable with the software and skills necessary for teaching online.…”
Section: Polarizing Coding Themesmentioning
confidence: 99%